Profiling of anti-diabetic agent from Pereskia Bleo (KUNTH) / Nadzrul Aida Bt Mat Darus - Mat Darus, Nadzrul Aida (2015)

(untitled)
Pereskia bleo (Kunth) belongs to the family of Cactaceae and locally known as jarum tujuh bilah. It has been used traditionally by native Malaysian for the treatment of diabetes. However, the lack of scientific data to validate such claim have motivates researcher to study for its anti-diabetic activities. In this study, the leaves, stems and roots of Pereskia bleo crude extracts were extracted with hexane, petroleum ether, chloroform, methanol and aqueous. The separation and detections of bioactive compounds were done using Thin Layer Chromatography (TLC) and Liquid Chromatography Mass spectrometry combined with Mass Spectrometry (LCMS/MS) methods. The TLC results showed the presence of terpenoid, alkaloid, phenolics acid and flavonoids in Pereskia bleo crude extracts. While in LCMS/MS analysis has revealed the presence of phenolics acid, amino acid, jasmonic acid or dihydroxymellein, Chrysin, Apigenin based compounds, Apigenin 6 C Glucoside, and Apigenin 7 Rutinoside in Pereskia bleo crude extracts. The total phenol content were highest in stem aqueous extract, root chloroform extract and leaves methanol extract at 6.06+0.1 mg GAE/g, 3.64+0.1 mg GAE/g and 3.00+0.1 mg GAE/g respectively. Whereas, the total flavonoids content were highest in stems , leaves and root chloroform extract at 11.07+0.7 mg QE/g, 5.2+0.7 mg QE/g and 3.40+0.7 mg QE/g respectively. The Glycogen Phosphorylase Inhibition bioassay (GPi) showed the highest percentage of GPi activity from roots, leaves and stems methanol extract of Pereskia bleo at 89.9%, 82.3% and 78.3% respectively. The acute toxicity test was performed using non-diabetic Sprague Dawley (SD) rats have showed none of the toxic signs occur such as anxiety, urination or defecation, pain response and death when administrated with 250, 500 and 1000mg/kg of Pereskia bleo aqueous extract. In Oral Glucose Tolerance Test (OGTT), the administration iii of Pereskia bleo aqueous extracts showed the improved of glucose tolerance in non-diabetic rats. The roots aqueous extracts of Pereskia bleo also showed a maximum reduction of blood glucose level when administered with 250mg/kg and 500mg/kg at 120 minutes with 20% and 21%. Followed by leaves and stem aqueous extracts of Pereskia bleo with 11% and 14% of reduction, respectively. In treatments of diabetic rats, the alloxan-induced diabetic rats showed that 500mg/kg of the leaves, stems and roots aqueous extracts of Pereskia bleo showed the significantly reduction in fasting plasma glucose levels by 66%, 65 and 58% (p<0.05) respectively on 25th day compared to diabetic control group. The treatments of Pereskia bleo aqueous extracts to diabetic rats showed the significantly (p<0.05) improved in body weight and decreased in liver enzymes levels (ALT, AST and ALP), renal function test (creatinine and urea) and serum lipid profile (Total cholesterol, triglyceride, LDL) compared to diabetic group. It is also showed a significantly (p<0.05) increased in HDL levels compared to diabetic group. Thus, this study discovered that bioactive compounds found in crude extract of Pereskia bleo might be useful as anti-hyperglycaemic agents and these finding might be a fundamental to the further research to prove the claimed made by traditional practitioner that has consumed Pereskia bleo as diabetes treatment.